Choice. - Choice (Marrickville, NSW : Australian Consumers' Association, 2007)
"We are the leading consumer advocacy group in Australia. Independent and member-funded, CHOICE is here to ensure that Australian consumers like you get a fair go. We want your voice to be heard loud and clear when it comes to anything consumer-related, from saving money to choosing the best products and services for your family, and we're constantly on the look out for dodgy or misleading practices that might stop you from getting the best deal. We've been around for more than 50 years, so whether it's campaigning for your rights, making shopping easier, testing products or giving unbiased advice about food, finance and health, CHOICE has the expertise to make sure you get the best information."--About us
CHOICE is an Australian not for profit consumer organisation, previously known as the Australian Consumers Association.
Title from title screen (viewed on 23 Oct. 2015)
Mode of access: Available online. Address as at 6/11/15
Selected for archiving
Keywords: Consumer protection -- Australia; Consumers' preferences -- Australia; Product safety -- Standards -- Australia; Quality of products -- Australia; Australian